1983
DOI: 10.1073/pnas.80.11.3466
|View full text |Cite
|
Sign up to set email alerts
|

Modification of T-cell proliferation and interleukin 2 production in mice infected with Trypanosoma cruzi.

Abstract: Acute infection of mice with Trypanosoma cruzi results in severe immunodepression and the appearance of autoimmune symptoms. In vitro, concanavalin A-stimulated T cells from spleens of infected animals could neither produce nor respond to interleukin 2. Interleukin 2 production was not restored by addition of exogenous interleukin 1, and proliferative response to concanavalin A was not restored by exogenous interleukin 2. A population of Thy-i-negative cells in the spleen of infected animals was shown to suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 11 publications
(7 reference statements)
7
51
0
1
Order By: Relevance
“…Suppression of the cellular immune response has been observed during the infection by protozoan parasites, including Leishmania donovani 56 and Trypanosoma cruzi. 23 There is also evidence that the response of T cells is systematically suppressed during the acute illness due to E. histolytica, as has been observed in animal models 57 and in patients with amoebic hepatic abscess. 49 Serum from E histolytica-infected gerbils 58 and immune sera from patients 25 selectively suppress T cell proliferation by inhibiting IL-2 and IFN-␥ production.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Suppression of the cellular immune response has been observed during the infection by protozoan parasites, including Leishmania donovani 56 and Trypanosoma cruzi. 23 There is also evidence that the response of T cells is systematically suppressed during the acute illness due to E. histolytica, as has been observed in animal models 57 and in patients with amoebic hepatic abscess. 49 Serum from E histolytica-infected gerbils 58 and immune sera from patients 25 selectively suppress T cell proliferation by inhibiting IL-2 and IFN-␥ production.…”
Section: Discussionmentioning
confidence: 78%
“…49 Serum from E histolytica-infected gerbils 58 and immune sera from patients 25 selectively suppress T cell proliferation by inhibiting IL-2 and IFN-␥ production. Previous studies have shown that in infections caused by pathogens that induce immunosuppression in the host, such as L. donovani, 56 HIV, 59 and T. cruzi, 23 the outcome of the relationship could be regulated by CD4+ helper T cells with different pattern of cytokines. Protective immunity would be associated with Th1 cells that produce INF-␥ and IL-2, whereas Th2 cells, which produce immunosuppressive IL-4 and IL-10, could facilitate the survival and dissemination of the parasite generating tissue damage and the appearance of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually we found that macrophage activating factor (MAF) is produced by TSST-1-stimulated T cells (unpublished data). It has been thought that lymphokines are essential in the regulation of the immune response (12) and the acquisition of resistance to microbial infections (13,14). In hosts infected with TSST-1-producing staphylococci, however, lymphokines including IL 2 are presumed to be produced in excess over the physiologically required amounts; substantial amounts of IL 2 and MAF were produced when HPBL were stimulated with 0.1-1 ng of TSST-1 per ml for 12-24 hr (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…The acute phase of Chagas' disease in mice is associated with a T cell defect characterized by a decreased production of IL-2 in response to parasite antigens and T cell mitogens [1][2][3]. In contrast, production of interferon-gamma (IFN-) during the second week of infection is increased, as indicated by accumulation of IFN-mRNA in spleen and increased in vitro secretion of IFN-by spleen cells [4].…”
Section: Introductionmentioning
confidence: 99%